Family Business - Viony Rahmawati; Rusnandari Retno Cahyani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Family business, businesses owned and inherited by family members, play an importantrole in the Indonesian economy. Despite its long-term benefits and legacy potential, familybusinesses are also challenging. In carrying it out, maintaining the good name of the family,providing business knowledge to family members, and overcoming difficulties in reachingagreements are key factors. Several figures such as Moores and Barrett, Marpa, Dussault, andPoza provide different views regarding the definition of a family company. However, thepoint is that this company is family owned, involved in management, and has the potential tobe sustainable across generations. In the Indonesian context, several successful familycompanies include PT. DJARUM, PT. Indofood Sukses Makmur, Trans Corp, Bakrie Group,and Sampoerna. Knowing the various types of promising family businesses, such asrestaurants, learning courses, plantation industries, automotive businesses, and eventorganizers, can be a guide for starting a sustainable family business.